2019
DOI: 10.3889/oamjms.2019.178
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Inhibition of Ethylacetate Fraction of Zanthoxylum Acanthopodium DC. Fruit against T47D Cells

Abstract: BACKGROUND: The use of medicinal plants is increasing in several decades for relief many diseases. Indonesia consists of thousands of islands with various plants and the manners of the community using plants as a treatment for every disease traditionally. AIM: Cytotoxic activity of ethyl acetate fraction (EAF) of Zanthoxylum acanthopodium fruit was tested towards T47D breast cancer cells. METHODS: The in vitro cytotoxic activity was performed by MTT assay, and the result was expressed as the IC50 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A concentration of 25 mg/mL is likely a safe concentration of Z. acanthopodium extract as an oral anti-inflammatory agent. The previous study reported that the IC50 of the Zanthoxylum acanthopodium extract was 48.94±0.32 µg/mL to T47D breast cancer cell lines 24 . Different solvents might affect the cytotoxicity effect of the extract; Satria et al's study used ethyl acetate, while our study used ethanol as solvent 24 .…”
Section: Discussionmentioning
confidence: 94%
“…A concentration of 25 mg/mL is likely a safe concentration of Z. acanthopodium extract as an oral anti-inflammatory agent. The previous study reported that the IC50 of the Zanthoxylum acanthopodium extract was 48.94±0.32 µg/mL to T47D breast cancer cell lines 24 . Different solvents might affect the cytotoxicity effect of the extract; Satria et al's study used ethyl acetate, while our study used ethanol as solvent 24 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous in vitro studies indicate that some of the compounds isolated from the genus Zanthoxylum exert their anticancer activity through induction of apoptosis and cell cycle arrest. 33,34 Based on the results of our in vitro antiproliferative activities, it was inferred that some of the isolated compounds reported herein inhibit cancer cell proliferation by causing cell cycle arrest and apoptosis. In that regard, we attempted to elucidate the probable anticancer mechanism of action of the isolated compounds against protein targets in the p53 pathway.…”
Section: In Silico Docking Studiesmentioning
confidence: 87%
“…Nanoherbal of ZA has high antioxidant and had extremely small-sized at 0.440 μm and based on particle size analysis, it has an average diameter of distribution of 783.9 ± 173.4 nm ( Situmorang et al, 2019a ). The cytotoxicity activities in this plant can through cell cycle arrest, reducing cyclin D1, and increasing the expression of p53 ( Satria et al, 2019 ). However, an n-hexane extract from ZA fruit given during the postimplantation period of 6–14 days had a negative effect on mice liver changed the colour and texture of the liver surface and increased damage to hepatocytes ( Sabri et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%